2001
DOI: 10.1002/bit.10003
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle‐dependent protein secretion by Saccharomyces cerevisiae

Abstract: Synchronized Saccharomyces cerevisiae cell populations were used to examine secretion rates of a heterologous protein as a function of cell cycle position. The synchronization procedure had a profound effect on the type and quality of data obtained. When cell synchrony was induced by cell cycle-arresting drugs, a significant physiological perturbation of cells was observed that obscured representative secretion data. In contrast, synchronization with centrifugal elutriation resulted in synchronized first-gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…On the other hand, Buchetics et al (2011) reported that P. pastoris recombinants clones exhibiting a high secretion level are mostly in the G2 and M phases of cell cycle. The relation between cell cycle phase and protein production has been described not only in yeasts (Frykman & Srienc, 2001) but also in mammalian cells (Charlet, Kromenaker, & Srienc, 1995). The eukaryotic cell cycle has been examined comprehensively in the model organism S. cerevisiae reviewed in Cid et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Buchetics et al (2011) reported that P. pastoris recombinants clones exhibiting a high secretion level are mostly in the G2 and M phases of cell cycle. The relation between cell cycle phase and protein production has been described not only in yeasts (Frykman & Srienc, 2001) but also in mammalian cells (Charlet, Kromenaker, & Srienc, 1995). The eukaryotic cell cycle has been examined comprehensively in the model organism S. cerevisiae reviewed in Cid et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…While maintaining maximal absorption rate of 10 4 pheromone molecules per second appears well within the expected biological regime, it is important to note that the estimated pheromone secretion rates required for efficient activation of the mating response (η ∼ 6,000 mol/s) appears exceedingly high. Although direct measurements of α-factor secretion rates are not available, corresponding estimates for protein secretion rate are on the order of magnitude of 10 molecules/second [23,24]. Moreover, since α-factor mRNA is present at only ∼10-50 copies per cell [25], it is unlikely that more than ∼100 mature α-factor molecules will be produced per second, considering a translation initiation rate of about ∼0.1-1 s −1 (rate limiting step), even when taking into account the fact that there are six repetitions of the peptide within the genome [26].…”
Section: Compatibility Of the "Perfect Sink" Hypothesismentioning
confidence: 99%
“…For example, maximum secretion rate of antibody had been found in the G2M phase of murine hybridoma cells (12). Experimental data derived from Saccharomyces cereVisiae had also shown that a heterologous protein of interest was mainly secreted during the late G2 and M phases (13,14). Thus, the accurate mathematical description of such processes and the control of the cell cycle specific products can only be achieved by using multi-staged models (5).…”
Section: Introductionmentioning
confidence: 96%